Incomplete hippocampal inversion and epilepsy: A systematic review and meta‐analysis. (16th December 2020) - Mutti, Carlotta; Riccò, Matteo; Bartolini, Yerma; Bernabè, Giorgia; Trippi, Irene; Melpignano, Andrea; Ciliento, Rosario; Zinno, Lucia; Florindo, Irene; Sasso, Enrico; Odone, Anna; Parrino, Liborio; et al.
Abstract: Objective: Incomplete hippocampal inversion (IHI) is a relatively frequent radiological finding at visual inspection in both epilepsy and healthy controls, but its clinical significance is unclear. Here, we systematically retrieve and assess the association between epilepsy and IHI using a meta‐analytic approach. Additionally, we estimate the prevalence of IHI in patients with malformation of cortical development (MCD). Methods: We systematically searched two databases (Embase and PubMed) to identify potentially eligible studies from their inception to December 2019. For inclusion, studies were population‐based, case–control, observational studies reporting on epilepsy and IHI. The risk of developing epilepsy in IHI (estimated with odds ratio [ORs]) and the frequency of IHI among patients with MCD are provided. Results: We screened 3601 records and assessed eligibility of 2812 full‐text articles. The final material included 13 studies involving 1630 subjects. Seven studies (1329 subjects: 952 epileptic and 377 nonepileptic) were included for the estimation of the risk of developing epilepsy in the presence of IHI. The estimated OR of active epilepsy in IHI was 1.699 (95% confidence interval = 0.880–3.281), with moderate heterogeneity across studies ( I 2 = 71%). Seven studies (591 patients) provided information about the frequency of IHI in MCD. Up to one third of patients with MCD (27.9%) presented coexistent IHI. Significance: The present findings confirm that IHI is commonly observed in patients with MCD especially in periventricular nodular heterotopia or polymicrogyria. However, the estimated OR indicates overall weak increased odds of epilepsy in people with IHI, suggesting that the presence of isolated IHI cannot be considered a strong independent predictor for epilepsy development. Clear‐cut neuroradiological criteria for IHI and advanced postprocessing analyses on structural magnetic resonance imaging scans are recommended to highlight differences between epileptogenic and nonepileptogenic IHI.